The impact of climate change on the household food security of upland rice farmers in Sidomulyo, Lampung Province, Indonesia - Ktut Murniati; abdul mutolib (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Murniati K, Mutolib A. 2020. The impact of climate change on the household food security of upland rice farmers in Sidomulyo, Lampung Province, Indonesia. Biodiversitas 21: 3487-3493.  Climate change in the agricultural sector, particularly food crops, significantly decreases the production, causing the anomaly influences of El-Niño (drought) and La-Nina (flood). Climate change will have an impact on food availability and accessibility, thereby disrupting the food security and vulnerability of farmer households. This study aimed to: analyze the livelihood vulnerabilities, determine the food security level, and assess the livelihood vulnerability on the food security of upland rice farmer households against climate change. This study was conducted in Sidomulyo Sub-district, South Lampung District. The samples were randomly selected among farmers, resulting in 66 selected farmers. The analysis included: the livelihood vulnerability index– intergovernmental panel of climate change (LVI-IPCC), food security index based on the Indonesian Institute of Sciences, and the Ordinal Model Logit (Ologit). The results showed that the upland rice farmer’s household had a livelihood vulnerability of 0.071, belonged to the medium category.  Most farmer households (77.27%) were categorized as food secure.   The “secure” category in the food security index is obtained if the upland rice farmers fulfill three criteria includes food availability, food stability, and food sustainability.  The strategy of climate change adaptation, rice price, and phonska fertilizer price affects the food security of farmers’ households.  Climate change adaptation strategies are indispensable for sustainable food security.